"Writing is hard and it calls for honesty" : an interview with Rolando Hinojosa-Smith - Tillman, Gábor (AMERICANA E-journal of American Studies in Hungary, 2013)
Novelist, poet, and educator Rolando R. Hinojosa-Smith was born January 21, 1929, in Mercedes, Texas. He received his doctoral degree from the University of Illinois-Urbana in 1969. Known for a series of novels set in the Rio Grande Valley of Texas, Hinojosa-Smith won Quinto Sol Award for Literature in 1972 for Estampas del Valle y otras obras, and the Premio Casa de las Americas in 1976 for his Klail City y sus alrededores. He is professor of creative writing at the University of Texas at Austin.